Financial Performance Analysis of Islamic Banks and Conventional Banks at Bank Syariah Indonesia and Bank Negara Indonesia 2021-2023 - Harahap, M. Guffar; Rozainun Haji Abdul Aziz; M. Radian Syah; Ami Nullah Marlis (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2025)
Introduction: Banking is a financial sector that plays an important role in circulating national and global money. An analysis of banking financial performance is necessary to maintain good money circulation. Objective: This study was conducted to determine the financial performance of Islamic and conventional banks, namely Bank Syariah Indonesia and Bank Negara Indonesia, for 2021-2023. Method: This study uses quantitative methods and secondary data. Data collection techniques are done through observation or research on the company's online media. Data analysis was carried out using financial ratios in banking, namely Capital Adequacy Ratio, return on assets, Return on Equity, Non-Performing loans, Operating Costs, Operating Income, and Loan-to-Deposit Ratio, by comparing the results of the analysis of the two banks with their average values. Results: The study's results show that Bank BSI excels in the Capital Adequacy Ratio, return on assets, and Non-Performing Loan ratios, which indicate that this bank has a strong strategy in risk management and sharia-based business expansion. Meanwhile, Bank BNI excels in the Return on Asset ratio, Operating Costs to Operating Income, and Loan to Deposit Ratio, which shows a better ability to manage assets, control operating costs, and maintain funding balance. Implications: These findings provide strategic insights for policymakers, banking management, and investors in evaluating the strengths and challenges of each banking model. Understanding the competitive advantages between Islamic and conventional banks can be a basis for financial decision-making and developing future banking industry policies.